Understanding the roles of activated porous carbon nanotubes as sulfur support and separator coating for lithium-sulfur batteries. (1st April 2018) - Huang, Jian-Qiu; Chong, Woon Gie; Zheng, Qingbin; Xu, Zheng-Long; Cui, Jiang; Yao, Shanshan; Wang, Chuanwei; Kim, Jang-Kyo
Abstract: Carbon nanotubes are chemically activated to create hierarchical multiscale porosity while maintaining an excellent electrical conductivity. The lithium-sulfur battery consisting of an activated carbon nanotube (aCNT)/sulfur cathode and an aCNT-modified separator with an optimal composition delivers an excellent reversible capacity of 621 mAh g −1 after 500 cycles at 0.5 C with an exceptionally low degradation rate of 0.043% per cycle. The fascinating performance arises from the ameliorating functional characteristics of aCNTs in both the two battery components. The highly porous, conductive aCNT network facilitates fast electron/ion transport and easy electrolyte penetration into the cathode, facilitating full utilization of active materials. The aCNT layer deposited on separator effectively constrains the polysulfide shuttling by physically blocking their migration to the anode while immobilizing polysulfides by strong adsorption onto the micropores of aCNT surface, as validated by microscopic images and molecular dynamic simulations. Graphical abstract: Highlights: ACNTs in the electrode enhance full utilization of active materials. The aCNT layer on separator constrains the polysulfide shuttling. The battery delivers a high capacity of 621 mAh g −1 after 500 cycles at 0.5 C. Interactions between CNTs and Li2S6 are studied by molecular dynamic simulations.